Neural Leprosy: A case report - Widiawaty, Alida; Sjamsoe-Daili, Emmy Soedarmi; Olivia, Taruli; Menaldi, Sri Linuwih; Marissa, Melani; Octaviana, Fitri (Journal of General - Procedural Dermatology and Venereology Indonesia, 2016)
Neural leprosy is characterized by neurological deficit without skin lesions, with a prevalence ranging from 1% to 17.7%. Diagnosis might be difficult and need a multidisciplinary approach. This is a case of axonal type motor and sensory polyradiculoneuropathy of the peripheral facial nerve. A 26-year-old woman was referred from the neurology clinic with facial paralysis, suspected as leprosy. Physical examinations were as follows: no skin lesions, left eye lagophthalmos, thickening of right lateral peroneal and bilateral posterior tibial nerves, sensory impairment, peripheral bilateral facial palsy, and wasting of bilateral distal small muscles of the hands, with normal autonomic function. Nerve Conduction Study revealed multiple demyelinating mononeuropathy of upper and lower extremities. Her serum anti-PGL-1 IgM level was 1721 μ/mL, but after three months of treatment with MDT-PB regimen, it increased to 2815μ/mL. Therefore, the treatment was switched to MDT-MB regimen and 30 mg prednisone. The patient is still undergoing treatment. There has been a slight improvement after treatment with MDT-MB regimen. Nerve biopsy is the gold standard for diagnosis but has its limitations. However, serological test of anti PGL-1 can be a marker and a useful tool as an additional test to confirm the diagnosis, especially for patients with nerve impairments. Difficulties are due to the absence of skin lesions and neuropathy which may be caused by other diseases. Both diagnosis and treatment require multidisciplinary approach. Treatment given is intended to correct nerve damage and prevent further disabilities. Click here to edit this text or paste your document here to convert it to HTML This demo allows you to test the features of this online HTML converter. Type in one of the fields and see the other one changing in real time! Set up the cleaning options and press ▼ Clean Work with any of the text areas and see the other one changing in real time: Left: Preview Right: Source code Preview how your document will look when published. Adjust the syntax highlighted HTML code.             Check out Pranx.com for nice online pranks.